(untitled) (Research, Society and Development, 2024)
Ulcerative keratitis, known as corneal ulcer, is characterized by the loss of the corneal epithelium, with exposure of the stroma. It has a multifactorial etiology and predisposition in some breeds, especially brachycephalic dogs. The present study aimed to carry out a literature review on the corneoconjunctival transposition technique for the treatment of ulcerative keratitis in dogs, determining its indications, methods and prognoses. Virtual research platforms and textbooks were used. The surgical technique of corneoconjunctival transposition consists of transposing an autologous pedicle of healthy cornea and respective bulbar conjunctiva to the site of the corneal defect. Through this study, it was possible to verify that the eyeball requires delicate and special handling as it is a complex and sophisticated organ, therefore, better treatment measures for ulcerative keratitis must be sought. Corneoconjunctival transposition presents promising results in the immediate postoperative period, preserving corneal innervation, corneal transparency and reducing the risk of graft rejection.